Influence of teaching resources on physical education teachers effectiveness in Kwara State, Nigeria - Ajadi, Memunat Tunrayo; Kayode, Falaye Elijah (International Journal of Educational Innovation and Research, 2022)
Effective teachers are those who achieved the aims and objective of education at large. It is in view of this that this paper examined influence of teaching resources on physical education teachers effectiveness in Kwara state, Nigeria. The objectives of the study were (i) determine the influence of use of instructional materials on teachers effectiveness in physical educationn (ii) assess the influence of curriculum on teachers effectiveness in physical educatin. The population was 250 teachers, while a sample of 150 respondents were used for the study. Two hypotheses were postulated and tested for the study. Questionnaire was used to collect data from the respondents and chi-square (x2) statistical tool was used to analyze the data. The findings revealed that use of instructional materials and curriculum are fundamental to teachers effectiveness in teaching physical education in schools. Sequel to the findings of the study, it was concluded that government should organized seminars and workshop for teachers in form of training and re-training programme so as to enhance their effectiveness in teaching and learning of physical education.